DEVELOPING A SUSTAINABLE BUSINESS EXCELLENCE MODEL AND DISCUSSING KEY FACTORS - Fan, Ping-Hsin; Chang, Wei-Lun (The South African Journal of Industrial Engineering, 2021)
To achieve sustainable growth and maintain competitive advantages, many companies consider the sustainability of society and the environment, and adopt the business excellence (BE) framework of quality awards to promote total quality management (TQM) activities. This study used the Malcolm Baldrige National Quality Award’s (MBNQA) business excellence evaluation standard as the main body, supplemented by the Dow Jones Sustainability Indexes (DJSI). It proposed scoring criteria for the sustainable business excellence model, and discussed the degree of cause and correlation between evaluation criteria. The key factors were explored to provide companies with a reference for the pursuit of sustainable business excellence.